Supporting learning in synchronous collaborative game design in virtual worlds: A synergy between technological and pedagogical considerations - Yu Xia; Shulong Yan; Mengying Jiang; Zipporah Brown (Computers & Education: X Reality)
Online collaboration has been ever present in our life and the same goes with collaborative learning in virtual worlds. However, little research has zoomed in on this type of collaborative learning context and we contribute to the understanding of technological infrastructure and pedagogical strategies to support collaborative learning in such a context. Taking a socio-material lens, we discuss four essential considerations in supporting collaborative design in virtual learning environments: social artifacts, togetherness, synchronicity, and multilevel participation. Cases were selected from a virtual makerspace offered in the summer of 2023 to illustrate the entanglement of technology and pedagogy. We then discuss in detail the technological and pedagogical considerations associated with these dimensions. Our framework provides concrete guidance for educators and researchers who are interested in offering or researching collaborative learning in virtual worlds.